Adaptive Fuzzy PID Control System for Satellite Earth Station Antenna Group Factor Based on Edge Calculation - Haibin SHAN; Yanjun SHI; Zijing LIU; Yuanhong LI; Wenhua ZHAO; Muquan HE; Chuzhou LI (天地一体化信息网络, 2023)
The antenna tracking control system of satellite ground receiving station generally adopts PID control.Due to the infl uence of various uncertain factors, it is diffi cult to obtain the optimal control parameters for this kind of system, resulting in the PID control eff ect is not ideal.An adaptive fuzzy PID antenna tracking control system based on edge computing was designed.The parameters of PID controller were adjusted in time by fuzzy control algorithm, and the optimal calculation of fuzzy control input and output domain was realized in edge computing server.The simulation results showed that the adaptive fuzzy PID antenna tracking control system based on edge calculation could achieve good control eff ect.